Poynting vector meter / Azlina Mohd Idris, Hasni Abdullah and Ruziah Mat Amin - Mohd Idris, Azlina; Abdullah, Hasni; Mat Amin, Ruziah (1994)
Poynting vector meter is a meter that is used to measure loss density in watt/m2 by multiplying two signals of electric field strength E and magnetic field strength H. The two signals come from a probe consists of a small coil for measuring H and sharp pins for measuring E. The directions of E and H are arranged to be perpendicular to each other in order to omit the effect of sin 0. The report consists of four main parts: Power circuit, Probe, Poynting vector meter ( practical electronic circuit) and Simulation of circuit on computer. To check up the circuit, the probe is fixed on a lossy conductive surface to sense the electric and magnetic field that will be the input to the poynting vector meter circuit and the output will be the loss density in watt / m 2 for different positions of the lossy conductor.